ANALISIS PENDAPATAN USAHATANI HOLTIKULTURA (Studi Kasus Agrowisata Awila Hills Kecamatan Molowe Kabupaten Konawe Utara) - Adam Adam; Bahari Bahari; Fahria Nadiryati Sadimantara (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This study aims to (1) determine the cost and income of horticultural farming in Awila Hills agro-tourism, Molawe District, North Konawe Regency. (2) analyze the types of plants that contribut e the largest income to horticultural farming in Awila Hills Agro-tourism, Molawe District, Nort Konawe Regency. This research was conducted in Awila Hills Agrotourism, Molawe District, Nort Konawe Regency. The sampling method in this study was determined by a proportional sampling technique, namely taking samples with certain considerations. The number of samples in this study amounted to 1 horticultural farming manager. The analytical method used is income analysis and RC Ratio analysis. Based on the results of this study, the income obtained by farmers in horticultural farming for two harvest seasons is Rp. 94.626.125. Based on RC Ratio analysis the type of plant that contributed the largest income to horticultural farming during the two harvest seasons was, long beans plant which was 4,79. So that tomato plants are more profitable in farming than other crops such as cayenne pepper, curly chili, corn, long beans, pumpkins, cabbage and tomatoes.